Processes and structural transformations in superficial layers of polymeric compos at loading friction - Кашицький, В.П.; Савчук, П.П.; Садова, О.Л. (Problems of Tribology, 2014)
As a result of complex investigation methods of controlling the structure and properties of ECM with different extent of polydispersive filling are grounded. The action of temperature and time parameters of treating on the mechanisms and kinetics of the processes of structurization of the developed composites is established. The effect of modifying components, complex ultrasonic, ultraviolet and magnetic treatment on reological, physical, mechanical and tribotechnical characteristics and processes of ECM structurization have been studied.